Roles of Nucleus Accumbens CREB and Dynorphin in Dysregulation of Motivation - Muschamp, John W. (Cold Spring Harbor Laboratory Press, 2013)
Psychostimulants such as amphetamine and cocaine are believed to produce dependence by causing rapid, supraphysiological elevations in synaptic dopamine (DA) within the nucleus accumbens (NAc) (Volkow et al. 2009, Neuropharmacology 56: 3–8). These changes in forebrain DA transmission are similar to those evoked by natural reinforcers (Louilot et al. 1991, Brain Res 553: 313–317; Roitman et al. 2004, J Neurosci 24: 1265–1271), but are of greater magnitude and longer duration. Repeated drug exposure causes compensatory neuroadaptations in neurons of the NAc, some of which may modulate excess DA in a homeostatic fashion. One such adaptation is the activation of the transcription factor CREB (cAMP response element-binding protein) within neurons of the NAc. Although elevated levels of transcriptionally active CREB appear to attenuate DA transmission by increasing expression of the endogenous κ opioid receptor (KOR) ligand dynorphin, increased dynorphin transmission may ultimately have undesirable effects that contribute to drug withdrawal states as well as comorbid psychiatric illnesses such as depression. This state may prompt a return to drug use to mitigate the adverse effects of withdrawal. This article summarizes our current understanding of how CREB and dynorphin contribute to the dysregulation of motivation and describes novel therapeutic strategies that derive from preclinical research in this area.